Circularly polarized near-infrared phosphorescence of chiral chromium(iii) complexes. Issue 13 (25th January 2023) - Cheng, Yang; He, Jiang; Zou, Wenjie; Chang, Xiaoyong; Yang, Qingqing; Lu, Wei
Abstract : Near-infrared 850 nm Cr(iii ) emissions with handedness in degassed solutions were induced by ligand carbon-centred chirality. Abstract : Homoleptic Cr(iii ) complexes containing anionic tridentate 1, 8-(bisoxazolyl)carbazolide ligands are phosphorescent in deaerated solutions with peak maxima in the range of 813–845 nm. The ligand carbon-centred chirality has been transferred to the helical chirality of the complexes and hence induced circularly polarized NIR-emissions with dissymmetry factor in the scale of 2.0 × 10 −3 .